The man standing on the globe - M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
The forthcoming 134th birthday of Nikolai Vavilov has in spired the editors to publish the essay The Man Standing on the Globe written by Dr. Margarita Vishnyakova as the introductory article to the Spanish translation of Vavilov’s Five Continents (Cinco continentes). This book was published in 2015 by Libros del Jata S.L., a small publishing company in Bilbao, Spain. Margarita Vishnyakova was directly involved in the process of publication. She was acquainted with Dr. Gustavo Renobales, a former professor of botany at the University of the Basque Country, who became the book’s editor and publisher. As soon as the publishing process was initiated, Gustavo sought Margarita’s aid. She helped to overcome formalities associated with copyright and assisted with translation and selection of illustrations, also contributing to the solution of some botanical and linguistic problems (Vishnyakova, 2017). It took two years to finalize the publication. This essay was published only in Spanish. The original Russian version is presented here.